Asymmetries in the Union Wage Premium in Ghana - Blunch, Niels-Hugo (Washington, DC: World Bank, 2014)
The article uses a matched employer-employee data set for Ghana and adopts a quantile regression approach that allows the effects of unionization to vary across the conditional wage distribution. It is shown that if there are intrafirm differences in unionization, there does appear to be a premium among poorer paid workers in the formal sector. Although this cannot be given a causal interpretation, it suggests important issues about how unions may affect one part of the labor market.